Social change in Kerala : insights from micro-level studies - Nair, K. N.; Menon, Vineetha; Project on Village Restudies on South India initiated by the Kerala Research Programme on Local Level Development (Delhi : Daanish Books, 2007)
Contributed articles developed as part of project on Village Restudies under the Kerala Research Programme as a collaborative effort among the prominent Social Science Research Institutes in South India
Includes index
Keywords: Social change -- India -- Kerala -- Case studies; Community development -- India -- Kerala -- Case studies; Village communities -- India -- Kerala; Kerala (India) -- Social conditions